2023
DOI: 10.1021/acsnano.2c10351
|View full text |Cite
|
Sign up to set email alerts
|

Augmenting Intracellular Cargo Delivery of Extracellular Vesicles in Hypoxic Tissues through Inhibiting Hypoxia-Induced Endocytic Recycling

Abstract: As mesenchymal stem-cell-derived small extracellular vesicles (MSC-sEVs) have been widely applied in treatment of degenerative diseases, it is essential to improve their cargo delivery efficiency in specific microenvironments of lesions. However, the interaction between the microenvironment of recipient cells and MSC-sEVs remains poorly understood. Herein, we find that the cargo delivery efficiency of MSC-sEVs was significantly reduced under hypoxia in inflammaging nucleus pulposus cells due to activated endoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 53 publications
0
5
0
Order By: Relevance
“…Oxygen sensing pathway was found to regulate endocytosis 38 . Previous studies have also demonstrated that intracellular cargo delivery of exosomes is undermined in hypoxic tissues 18 . Therefore, EBO is expected to restore exosome delivery efficiency in hypoxic microenvironments by supplying oxygen.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Oxygen sensing pathway was found to regulate endocytosis 38 . Previous studies have also demonstrated that intracellular cargo delivery of exosomes is undermined in hypoxic tissues 18 . Therefore, EBO is expected to restore exosome delivery efficiency in hypoxic microenvironments by supplying oxygen.…”
Section: Resultsmentioning
confidence: 99%
“…Notably, exosomes offer several advantages over stem cells, as they are considered safer, lack tumorigenic potential, and pose a minimal risk of embolism 16 , 17 . Nevertheless, recent investigations have revealed that the intracellular cargo delivery efficiency of exosomes is compromised under wound hypoxic conditions due to activated hypoxia-induced endocytic recycling 18 , 19 . This limitation significantly impedes their therapeutic efficacy and necessitates approaches to enhance exosome delivery in hypoxic wound tissues.…”
Section: Introductionmentioning
confidence: 99%
“…The modified EVs restored the cellular uptake rate, delivered Prx2 into NP cells and inhibited TNF-αinduced pyroptosis. In another study, Tong et al [34] investigated whether the delivery efficiency of MSC-EVs was decreased in NP cells under hypoxic conditions because of an increase in endocytic recycling. Hypoxia inducible factor-1 (HIF-1)-induced upregulation of Rabcoupling protein (RCP), which is also known as RAB11 family interacting protein 1 (RAB11FIP1), promoted the Rab11a-dependent recycling of internalized MSC-EVs by facilitating the interaction between Rab11a and MSC-EVs.…”
Section: Discussionmentioning
confidence: 99%
“…Significant progress has been made in the treatment of IDD by MSCs, but due to the harsh environment of the IDs[ 5 ], the therapeutic effect of MSCs is reduced due to the lack of oxygen in the environment[ 61 ]. However, it has been found that the differentiation of MSCs to chondrocytes under hypoxic conditions can be helped by the addition of leptin[ 62 ], which provides energy for cell differentiation through its dependent glycolysis.…”
Section: Harsh Environment Of the Idmentioning
confidence: 99%